2006
DOI: 10.1007/s11517-006-0074-9
|View full text |Cite
|
Sign up to set email alerts
|

Finite element contact analysis of the hip joint

Abstract: The hip joint plays an important role in the musculoskeletal system; however, current knowledge of the mechanics of the hip joint, especially with regard to the distribution of stress, remains limited. In experimental research, difficulties arise during reproduction of physiological conditions of daily activities and practicable measurement of locations inside the hip joint without violating the physiological environment. On the other hand, numerical approaches, such as finite element analysis, have become use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 19 publications
4
51
0
Order By: Relevance
“…The maximum value with CE ¼ 188 was 3.5 MPa, which is quite consistent with our results (3.5 MPa for CE ¼ 208). The recent finite element analysis conducted by Bachtar et al 20 reported the contact pressure as 5.5 MPa, not mentioning the effect of acetabular geometry. Although our results agree with previous computational models in normal joints, the range of contact pressure calculated in our study is higher (up to 16.5 MPa for severe impingement), which was not reported in previous computational models.…”
mentioning
confidence: 99%
“…The maximum value with CE ¼ 188 was 3.5 MPa, which is quite consistent with our results (3.5 MPa for CE ¼ 208). The recent finite element analysis conducted by Bachtar et al 20 reported the contact pressure as 5.5 MPa, not mentioning the effect of acetabular geometry. Although our results agree with previous computational models in normal joints, the range of contact pressure calculated in our study is higher (up to 16.5 MPa for severe impingement), which was not reported in previous computational models.…”
mentioning
confidence: 99%
“…Muscles and ligaments were not included in the model. Instead, their effect on the hip joint was replaced by applying the load to the femoral head [17]. To avoid rigid rotations and improve stability, 12 springs were applied around the joint (k = 1 N/mm).…”
Section: Boundary Conditions and Loadingmentioning
confidence: 99%
“…where 1 C , 2 C , 3 C and 4 C are four different kind of cliques. Each involving three pixels, which can be visualized as in Fig.…”
Section: Prior Energymentioning
confidence: 99%
“…As a consequence, image segmentation and volumetric mesh generation are two inevitable steps to be performed. Whereas image segmentation can be performed semi-or fully automatically with some acceptable accuracy, automatic volumetric meshing algorithms are prone to errors and dependent on object topology, desired boundary conditions [1], etc. Therefore semi-manual techniques are often used, which is tedious and time consuming.…”
Section: Introductionmentioning
confidence: 99%